Narrating Motherhood: The Power of Storytelling - Lénárt-Muszka, Zsuzsanna (Hungarian Journal of English and American Studies, 2021)
Book review: Martin, BettyAnn, and Michelann Parr, eds. Writing Mothers: Narrative Acts of Care, Redemption, and Transformation. Bradford, ON: Demeter P, 2020. 258 pages. ISBN 978-1-77258-223-9. Pbk. 34.95.